Pengaruh Self-Efficacy, Quality of Work Life, dan Work Engagement terhadap Kinerja Karyawan - Sava Risky Tarisya; Kasmari (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The purpose of this study is to analyze and examine the influence of self-efficacy, quality of work life, and work engagement on employee performance at KSPPS Nur Insani. This research employs a quantitative approach with an explanatory research design to investigate the effects of self-efficacy, quality of work life, and work engagement on employee performance at KSPPS Nur Insani Semarang. A non-probability sampling technique was applied using a saturated sampling method. Data were collected through questionnaires distributed to 45 employees of KSPPS Nur Insani, and subsequently analyzed using SPSS. The results indicate that self-efficacy, quality of work life, and work engagement each exert a positive and significant influence on employee performance. Based on these findings, it can be concluded that enhancing self-efficacy, improving the quality of work life, and fostering work engagement play a crucial role in strengthening employee performance at KSPPS Nur Insani.